Analisis Gerakan Literasi Sekolah di Sekolah Dasar - Dian Pujiati; Moh Aniq Khairul Basyar; Arfilia Wijayanti (Institut Agama Islam Negeri Palopo, 2022)
The purpose of this study was to determine the implementation of the School Literacy Movement, the obstacles to implementing the School Literacy Movement and also efforts to overcome the obstacles to the implementation of the School Literacy Movement in SD Negeri 01 Banjarejo, Karanganyar District, Pekalongan Regency. This study uses a qualitative method with a descriptive approach. The data collection procedure in this study used interviews, questionnaires, observation, and documentation techniques. The results showed that the implementation of the School Literacy Movement at SD Negeri 01 Banjarejo had been going well. Three stages of school literacy, namely the habituation stage, the development stage, and the learning stage have been fulfilled, one of which is reading 15 minutes before learning. The obstacles to implementing the School Literacy Movement include time constraints because face-to-face learning is limited and students' enthusiasm for reading and visiting the library is still lacking. Efforts to overcome obstacles in implementing the School Literacy Movement are by implementing reading strategies, giving awards, and providing motivation and facilities for students. Based on the results of filling out student questionnaires, on average students can read fluently, interest in reading is quite high, reading activities 15 minutes before class run regularly, students are more interested in reading picture books, and students are able to find learning resources independently.